Patterns of immune evasion in triple-negative breast cancer and new potential therapeutic targets: a review - Lucía Serrano García; Beatriz Jávega; Antonio Llombart Cussac; Antonio Llombart Cussac; Antonio Llombart Cussac; María Gión; José Manuel Pérez-García; José Manuel Pérez-García; Javier Cortés; Javier Cortés; Javier Cortés; María Leonor Fernández-Murga (Frontiers in Immunology)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer characterized by the absence of progesterone and estrogen receptors and low (or absent) HER2 expression. TNBC accounts for 15-20% of all breast cancers. It is associated with younger age, a higher mutational burden, and an increased risk of recurrence and mortality. Standard treatment for TNBC primarily relies on cytotoxic agents, such as taxanes, anthracyclines, and platinum compounds for both early and advanced stages of the disease. Several targeted therapies, including bevacizumab and sunitinib, have failed to demonstrate significant clinical benefit in TNBC. The emergence of immune checkpoint inhibitors (ICI) has revolutionized cancer treatment. By stimulating the immune system, ICIs induce a durable anti-tumor response across various solid tumors. TNBC is a particularly promising target for treatment with ICIs due to the higher levels of tumor-infiltrating lymphocytes (TIL), increased PD-L1 expression, and higher mutational burden, which generates tumor-specific neoantigens that activate immune cells. ICIs administered as monotherapy in advanced TNBC yields only a modest response; however, response rates significantly improve when ICIs are combined with cytotoxic agents, particularly in tumors expressing PD-L1. Pembrolizumab is approved for use in both early and advanced TNBC in combination with standard chemotherapy. However, more research is needed to identify more potent biomarkers, and to better elucidate the synergism of ICIs with other targeted agents. In this review, we explore the challenges of immunotherapy in TNBC, examining the mechanisms of tumor progression mediated by immune cells within the tumor microenvironment, and the signaling pathways involved in both primary and acquired resistance. Finally, we provide a comprehensive overview of ongoing clinical trials underway to investigate novel immune-targeted therapies for TNBC.